Effect of Remimazolam and Propofol on Blood Glucose and Serum Inflammatory Markers in Patients with Type 2 Diabetes: A Clinical Trial with Prospective Randomized Control - Sang Hun Kim; Sang Min Yoon; Ji Hye Ahn; Yoon Ji Choi (Medicina)
Background and Objectives: Patients with type 2 diabetes are at a higher risk of postoperative complications, such as infections, delayed wound healing, and increased mortality compared to non-diabetic patients. Materials and Methods: This prospective randomized study aims to compare the effects of two anesthetics, remimazolam and propofol, on blood glucose levels and immune function in diabetic patients undergoing surgery. Seventy-four diabetic patients undergoing general anesthesia were randomly assigned to receive either remimazolam or propofol. Plasma blood glucose levels, anti-inflammatory markers, and insulin levels were measured during the perioperative period. Results: No statistically significant differences were observed between the remimazolam and propofol groups in terms of neutrophil-to-lymphocyte ratio, anti-inflammatory markers, or glucose levels during the perioperative period (p value > 0.05). Conclusions: These results suggest that there is no difference between propofol and remimazolam in immune function deterioration that occurs due to surgical stress. This study is limited by its small sample size, and in future, larger trials could be conducted to find differences in the effects of blood sugar levels and serum inflammatory markers between the two groups.